Improvement of special training of weight-lifters by means of various groove machines in the preparatory period at the stage of preliminary basic preparation - Oleksandr Piven (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to improve special training of heavyweights of 14-16 years old by means of various groove machines in the preparatory period at the stage of preliminary basic preparation. Material & Methods: 30 young weight-lifters at the age of 14-16 years were involved to the experiment; all of them had II and III sports categories. Results: it is revealed that sportsmen of the experimental group, who used nonconventional methods of training on special groove machines such as medicine ball, Sandbag, rubber tube, with the general training loads of classical technique of trainings, which has made 779 raising of the bar, equal to 90 tons, improved power indicators in the sum of double-event on 16,5 kg after the experiment, and also set own records unlike the control group, which trained by the traditional technique and used the loading volume, which has made 910 raising of the bar and 111 tons, and has improved power results on 7,2 kg. Conclusions: it is established that use of these machines promotes more effective development of high-speed-power and power qualities and consequently, leads to the growth of sports results in weightlifting.